Glucosinolates or erucic acid, which one contributes more to volatile flavor of fragrant rapeseed oil?. (30th June 2023) - Liang, Qiang; Xiong, Wei; Zhou, Qi; Cui, Cheng; Xu, Xia; Zhao, Ling; Xuan, Pu; Yao, Yingzheng
Graphical abstract: Highlights: Eighty-seven key odorants were identified in fragrant rapeseed oil. Methyl furfuryl disulfide with highest ROAV was first identified in rapeseed oil. Rapeseed oil flavor was affected by glucosinolates rather than erucic acid. SiO2 adsorbing is an effective alternative method to water degumming. Abstract: This study aims to investigate the effect of three rapeseed varieties with different erucic acid (EA) and glucosinolates (GLSs) content, and different degumming methods on the volatile flavor profiles of fragrant rapeseed oil (FRO). A total of 171 volatile compounds were identified by headspace solid-phase microextraction combine with gas chromatography-mass spectrometry (HS-SPME/GC–MS), and 87 compounds were identified as key odorants owing to their relative odor activity values (ROAV) ≥ 1. Methyl furfuryl disulfide was identified in rapeseed oil for the first time, with highest ROAVs (up to 26805.46). The volatile flavor profile of rapeseed oil was affected by GLSs content to a certain extent rather than EA content. Rapeseed varieties with low-EA and high-GLSs are suitable to produce FRO. Silicon dioxide adsorbing was an effective alternative method to water degumming in FRO. This work provided a new idea for selection of raw materials and degumming methods in FRO production.